The Impact of Microteaching Practices on EFL Students’ Teaching Skills and Confidence in Teaching English to Young Learners - Dudy Gunawan, Iwan (JOMANTARA, 2025)
This study explores the impact of microteaching practices on EFL undergraduate students’ teaching skills and self-confidence in preparing to teach English to young learners (TEYL). Conducted with 12 participants enrolled in a TEYL course, the research applied a mixed-methods approach involving pre- and post-tests and thematic analysis of reflective journals. The teaching skills assessed included classroom management, instructional clarity, use of child-centered strategies, and the ability to actively engage young learners. Results showed a marked improvement in both pedagogical competence and confidence following a series of microteaching sessions. Statistical analysis using paired-sample t-tests confirmed significant differences between pre- and post-intervention scores. Qualitative data further revealed enhanced student awareness of effective TEYL practices and growing readiness for classroom teaching. The findings suggest that microteaching is a valuable pedagogical tool, not only for building instructional proficiency but also for developing the emotional and psychological readiness needed to teach young learners. This study highlights the need for experiential learning in TEYL teacher preparation programs.